2023
DOI: 10.3390/agronomy13102654
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Fertilizer Effect of Bioprocessed Brewers’ Spent Grain by Microbial Consortium Addition

Davide Assandri,
Angela Bianco,
Niccolò Pampuro
et al.

Abstract: Brewers’ spent grain (BSG) is primarily recycled as livestock feed due to its high fiber content, undegradable protein, and water-soluble vitamins. However, BSG composting represents a possible alternative to organic waste management. Adding a microbial consortium further enhances the agronomical properties of the compost intended for fertilizing applications. Microbial-based fertilizers (plant growth-promoting microorganisms, PGPM) are a means to mitigate the adverse environmental impacts of excessive or impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In our previous study (Assandri et al, 2023), we evaluated positively the short-term benefits, not only as amendments but also as fertilizers, arising from the use of BSG-based substrates on lettuce growth. Additionally, we observed that both the pelleted compost and pelleted microbial-enriched compost contribute to a more active and diverse soil microbial community compared to NPK fertilization, leading to an improvement in soil quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study (Assandri et al, 2023), we evaluated positively the short-term benefits, not only as amendments but also as fertilizers, arising from the use of BSG-based substrates on lettuce growth. Additionally, we observed that both the pelleted compost and pelleted microbial-enriched compost contribute to a more active and diverse soil microbial community compared to NPK fertilization, leading to an improvement in soil quality.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study (Assandri et al, 2023), we assessed the effects on lettuce growth in a short-term pot experiment, using plants as a test subject. BSG-based compost and pelletized compost, both enriched with a microbial consortium as fertilizers intended to replace chemical fertilizers, were compared.…”
Section: Introductionmentioning
confidence: 99%